The mediating role of workplace spirituality on the relationship of Meaning of Life and family cohesion of teachers in COVID-19 - Zaeimzadeh, Seyed Mahdi; Jafari, Asghar (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the mediating role of workplace spirituality on the relationship of Meaning of Life and family cohesion of teachers in COVID-19. Methods: Method was descriptive- correlation. Population was married woman and man teachers of elementary schools in academic year 2020-2021 in the region 18 of Tehran. According to the table of Krejcie & Morgan (1970) and using multi cluster sampling 175 participants with inclusion criteria were selected and completed the questionnaires of Samani, s (2006) family cohesion, Milliman, s workplace spirituality and Salehi, s (2005) Meaning of Life. Data were analyzed by Pearson correlation and hierarchy regression. Results: The results indicated that there is a positive and significant relationship between Meaning of Life and family cohesion of teachers in COVID-19 (p<0.01). The results of hierarchy regression showed that workplace spirituality significantly mediate on the relation of Meaning of Life and family cohesion of teachers in COVID-19 (P<0.01). Conclusion: The results show evidence that meaning of life increase family cohesion of teachers through moderate conceptualization in work and marital life. Workplace spirituality indirectly effects they conceptualize moderately and efficiently meaning of life. Therefore, in order to promote family cohesion of teachers in COVID-19, it is necessary, pay attention to their meaning of life and workplace spirituality.